Degenerative Cervical Myelopathy: Development and Natural History [AO Spine RECODE-DCM Research Priority Number 2]. Issue 1 (February 2022) - Nouri, Aria; Tessitore, Enrico; Molliqaj, Granit; Meling, Torstein; Schaller, Karl; Nakashima, Hiroaki; Yukawa, Yasutsugu; Bednarik, Josef; Martin, Allan R.; Vajkoczy, Peter; Cheng, Joseph S.; Kwon, Brian K.; et al.
Study Design: Narrative review. Objectives: To discuss the current understanding of the natural history of degenerative cervical myelopathy (DCM). Methods: Literature review summarizing current evidence pertaining to the natural history and risk factors of DCM. Results: DCM is a common condition in which progressive arthritic disease of the cervical spine leads to spinal cord compression resulting in a constellation of neurological symptoms, in particular upper extremity dysfunction and gait impairment. Anatomical factors including cord-canal mismatch, congenitally fused vertebrae and genetic factors may increase individuals' risk for DCM development. Non-myelopathic spinal cord compression (NMSCC) is a common phenomenon with a prevalence of 24.2% in the healthy population, and 35.3% among individuals >60 years of age. Clinical radiculopathy and/or electrophysiological signs of cervical cord dysfunction appear to be risk factors for myelopathy development. Radiological progression of incidental Ossification of the Posterior Longitudinal Ligament (OPLL) is estimated at 18.3% over 81-months and development of myelopathy ranges between 0-61.5% (follow-up ranging from 40 to 124 months between studies) among studies. In patients with symptomatic DCM undergoing non-operative treatment, 20-62% will experience neurological deterioration within 3-6 years. Conclusion: Current estimates surrounding the natural history of DCM, particularly those individuals with mild or minimal impairment, lack precision. Clear predictors of clinical deterioration for those treated with non-operative care are yet to be identified. Future studies are needed on this topic to help improve treatment counseling and clinical prognostication.